Selección de ovocitos competentes, utilizando el factor de crecimiento nervioso (NGF) y el factor de crecimiento vascular endotelial (VEGF), con el fin de aumentar las posibilidades de embarazo en pacientes que se encuentran en tratamientos de fecundación - Salguero R., Rodrigo; Miranda V., Cristián; Carvajal M., Antonio; Romero O., Carmen (Revista Hospital Clínico Universidad de Chile, 2010)
The attention from embryologist toward the assessment of oocyte quality in human in vitro fertilization (IVF) is increasing every day. Oocyte selection and the identification of the best oocytes, in fact, would help to limit embryo overproduction and to improve the results of oocyte cryostorage programs. Multiple methods have been proposed; but a good correlation between specific biochemical characteristics and measurable oocyte quality-linked, embryo-related variables has not been established to date. In IVF programs that include oocyte selection, levels of vascular endothelial growth factor (VEGF) and neural growth factor (NGF) could be used as an index to exclude oocytes that developed in a hypoxic follicle. The presence of both ovarian angiogenic factors provides an ideal environment to maintain the cyclical changes in vascular density that occurs during follicular development. NGF would act within a short time-frame to replenish the supply of VEGF required for the vascularization of growing preovulatory follicles and perhaps newly formed corpora lutea. Levels of these angiogenic factors can predict the necessary vascular changes within the follicles and the competence of the oocytes. A hypoxic status at this level could be responsible for the high intrafollicular and plasma concentrations of VEGF and for the low quality of the oocytes.